2004
DOI: 10.1007/s00428-004-1103-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of annexin II in conventional renal cell carcinoma is correlated with Fuhrman grade and clinical outcome

Abstract: Conventional renal cell carcinomas (CRCCs) were investigated for the expression of annexin II (ANX II) to determine out whether this calcium-binding protein could serve as a useful prognostic marker. CRCCs and adjacent nonneoplastic tissue from 33 patients were investigated for ANX II by immunohistochemistry, RT-PCR, and western blot analysis. ANX II expression was correlated with tumor differentiation (Fuhrman grade) and to clinical outcome. Tumors were composed of ANX II positive and negative cells. In grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 26 publications
2
58
1
1
Order By: Relevance
“…Some of the annexins have been well characterised while less is known about the biology of some of the other Figure 3 The mean intensity of expression of individual annexins in normal colon, primary colorectal cancer and lymph node metastasis. Zimmermann et al, 2004aZimmermann et al, , b, 2007Syed et al, 2007). However, the annexin profile has not previously been investigated in individual tumour types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the annexins have been well characterised while less is known about the biology of some of the other Figure 3 The mean intensity of expression of individual annexins in normal colon, primary colorectal cancer and lymph node metastasis. Zimmermann et al, 2004aZimmermann et al, , b, 2007Syed et al, 2007). However, the annexin profile has not previously been investigated in individual tumour types.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 shows increased expression in several type of cancer, including renal cell cancer (Zimmermann et al, 2004a), breast cancer (Sharma et al, 2006) and sarcomas (Gillette et al, 2004;Syed et al, 2007), and there are several possible mechanisms by which annexin A2 may be involved in tumour progression. Annexin A2 interacts with tissue-type plasminogen activator and disruption of this interaction resulted in decreased tumour cell invasion (Rand, 2000;Diaz et al, 2004;Sharma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an in vitro study of rat RCC showed an association between ANX2 overexpression and metastasis (Tanaka et al, 2004). In addition, another report showed that ANX2 expression correlated with higher nuclear grade of the tumour and poor clinical outcome, although the study included only 33 cases (Zimmermann et al, 2004). These findings imply that ANX2 may be involved in the metastatic process in RCC.…”
mentioning
confidence: 91%